The wreck & rise of Whitson Mariner - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith). Tales of Old Natalia, 2018)
King Whitson Mariner leads the displaced rabbits as they weather every challenge on their quest for a new home.